Electrochemical dissolution of PtRu/C: Effect of potential, fuels, and temperature - Minichová, Mária; Priamushko, Tatiana; Hutzler, Andreas; Hrbek, Tomáš; Khalakhan, Ivan; Mayrhofer, Karl J.J.; Cherevko, Serhiy (Electrochimica Acta, 2024)
Over the last decade, in situ or online inductively coupled plasma mass spectrometry (ICP-MS) has been established as a powerful tool for time- and potential-resolved assessment of electrocatalyst dissolution stability. On the other hand, much more accessible for practical realization ex situ ICP-MS studies in three-electrode cells are not commonly carried out. Still, they can offer valuable insights into catalyst degradation during prolonged accelerated stress tests, thus complementing the online measurements. This work presents an example of how both techniques can be used jointly to study the effect of potential, fuels (isopropanol and glycerol), and temperature on PtRu/C dissolution. PtRu/C is chosen for its potential use as an electrocatalyst in fuel cells and electrosynthesis. Ru is a significantly less noble metal, so it is anticipated to dissolve preferentially, resulting in a loss of the electrocatalyst's functionality. Elucidating more light into dissolution behavior and the environment's role can help develop mitigating strategies to minimize such degradation. Our study reveals that potential has a significant effect on the dissolution of both metals. On the contrary, fuels only affect Ru dissolution, with trends varying depending on the fuel. Temperature again affects the stability of both metals, increasing Pt dissolution with temperature. In the case of Ru, however, in certain conditions, metal dissolution decreases at an elevated temperature. Two additional complementary surface-sensitive techniques, i.e., Cu underpotential deposition and transmission electron microscopy, were used to investigate how Pt and Ru dissolution change their surface concentration. The finding opens the possibility of PtRu/C lifetime prolonging at applications where the potential reaches up to 1.0 VRHE.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Alcohol oxidation; Electrocatalysis; Electrosynthesis; Fuel cell; ICP-MS; Stability